Patterns of distribution, abundance and community composition of rock pool fishes in Goukamma Nature Reserve, South Africa - Purchase, David Bryce (Department of Oceanography, 2018)
Rock pools can be found in most rocky intertidal marine environments across the globe. Despite the vast body of literature describing the organization of ecological communities and biota inhabiting the greater rocky intertidal, very little effort has been given to rock pools. As a result they are far less understood than the adjacent emergent intertidal, particularly with respect to their fish communities. This is mostly due to the relative small size of rock pool fishes, their cryptic behaviour and morphologies, the relative difficulty in sampling intertidal fish utilizing conventional methods, and the low economic value of rock pool fishes. Rock pool fishes may have significant ecological value, as they are involved in structuring intertidal communities. Due to reduced environmental fluctuations within rock pools, these habitats may serve as crucial refuges from adjacent stressors. Furthermore, rock pools may play an important role in the early life histories of sub-littoral fish species that utilize these habitats as juveniles, some of which are valuable to fisheries as adults. It has been suggested that due to the lack of exposure at low tide, rock pools do not represent a true intertidal habitat, as organisms are not subject to the full range of environmental fluctuations seen in adjacent habitats. There is unequivocal evidence indicating that, like the surrounding emergent substrata, conditions in rock pools are highly regulated by the tidal cycle and that the degree of environmental fluctuations will vary greatly with intertidal height and degree of exposure of individual pools, much like patterns seen in adjacent habitats. Fishes inhabiting rock pools can be broadly categorised into groups based on their major zoographic provinces, life history traits and their behavioural affinities, on top of basic taxonomic categorizations. Global patterns indicate two main rock pool fish communities, those of Gondwanan origin and those of Laurasian origin. South African rock pools are relatively well studied from a taxonomic perspective compared to elsewhere, however, like the rest of the globe, factors influencing their fish communities are far less understood. The aim of this study was to determine which, if any, physical and biological rock pool characteristics have any significant influence on the Abundance, Diversity and Community of fishes at Goukamma MPA, South Africa. This site was chosen due to a lack of previous surveys of rock pool fishes at this site and because of a need for an inventory of faunal communities in protected areas in South Africa. The shoreline within the reserve is dominated by sandy shores and interspersed with mixed rock-based habitats. Aelonite platforms form mixed shores and are found along areas west of the Goukamma estuary. Hard, predominantly older Table Mountain Sandstone layers are found along the eastern shore near Buffalo Bay. Rock pools are found at both shore types. Aelonite platforms were formed geologically recently from sand dunes formed during the interglacial periods of the Pleistocene and as a result are relatively flat and easily eroded into circular pools by loose rocks. The hard table mountain sandstone pools formed in cracks and faults caused by geological tilting action, and tend to long and thin rather than circular. Fifty-five rock pools were sampled, to investigate the influence of spatial (Location and Headland), temporal (Season), abiotic (Area, Height, Depth, Rugosity) and biological (Rock, Algae,) characteristics of rock pools on the distribution, abundance, diversity and community composition of rock pool fishes. A total of 747 fishes, representing seven families and 16 species were collected, using a non-lethal anesthetic, clove oil. Clinus cottoides, Parablennius cornutus and Caffrogobius caffer were the most dominant species, together making up almost 85% of the fish community. Total fish Abundance was not found to significantly change with any of the variables. The Shannon-Wiener Species Diversity Index for the whole of Goukamma was 1.64, however, it differed significantly among Locations, was greatest in pools of larger Area, lower Heights and higher cover of Rock. Community was found to significantly change with Location and was significantly influenced by Area, Rugosity, Height and Depth. Rock pool fish communities in South Africa show clear biogeographical patterns. These patterns show five distinct bioregions along the South African coastline in that familial distributions tend to be broken by the same oceanographic barriers seen in the distributions of many other marine taxa. The results suggest that rock pool fishes tend to exhibit distinct preferences to pools of certain typology and will seldom move over even small distances in search of new pools. Overall the study followed past findings from studies of similar type, both within South African and elsewhere.